ST JOSEPH AS PREFIGURED IN THE OLD TESTAMENT AND HIS ROLE IN THE REDEMPTIVE MYSTERY OF GOD - Kakkanattu, Joy Philip (Asian Horizons, 2022)
St Joseph is portrayed in the Bible with a theologically rich and pregnant word righteous (dikaios in Greek, and zaddiq in Hebrew). However, the nuances of this word are very profound and rich as is demonstrated from the life of St Joseph. St Joseph in his quality of zaddiq is prefigured in Biblical characters like Noah, Patriarch Joseph. There is also the possibility of tracing thematic foreshadowing of St. Joseph like Abraham’s faith, Moses’ risk-taking attitude, Ark of the Covenant, prophet as sentinel etc. St Joseph in the line of these foreshadowed personalities and themes plays an important role in the redemptive or salvific mystery of God as the foster-father of Jesus.